Gerakan EISGU (Ethical and Islamic Gadget Use) sebagai Solusi Pendidikan dalam Menghadapi Tantangan Jam Malam bagi Anak-Anak di Lhokseumawe - Zainul Mujtahid; Muh Fahrudin Alawi; Said Fadlan Anshari; Islami Fatwa (Progran Studi Farmasi Universitas Mandala Waluya, 2026)
The EISGU Movement (Ethical and Islamic Gadget Use) was implemented as a community service initiative to address the growing issue of excessive gadget use among adolescents during the night curfew policy in Blang Pulo Village, Lhokseumawe. The program aimed to foster ethical, Islamic, and productive digital behavior through an integrative educational approach combining religious values, character formation, and digital literacy. Conducted at SMPN 8 Lhokseumawe with 25 student participants, the program consisted of four main components: (1) Digital Ethics Education Based on Islamic Principles, (2) Educational Digital Content Creation Workshops using AI tools such as Gemini AI and ChatGPT, (3) Basic Programming (Coding) Workshops using Google Colab, and (4) the EISGU Declaration. Program effectiveness was evaluated by teacher observers using a rubric with seven indicators rated on a 4-point scale, yielding an overall effectiveness score of 3.8 out of 4, which indicates a very high level of achievement across ethical understanding, engagement, creativity, and responsible gadget use. These findings demonstrate that integrating Islamic values with digital literacy and AI-assisted learning enhances adolescents’ moral awareness, self-control, and 21st-century technological competencies, positioning the EISGU Movement as an innovative, faith-based educational model with strong potential for replication in other communities facing similar digital challenges.